Persepsi Pengunjung tentang Keberadaan Corner di Perpustakaan Universitas Negeri Padang - Bellini, Melani Putri; Nabila, Jeihan (Lembaga Yasin AlSys, 2025)
The utilization of corner services in college libraries, which remains minimal, indicates a gap between the availability of facilities and users' understanding of their functions. This study aims to describe the perceptions of visitors and librarians regarding the presence of corner services at the Information and Library Center of Universitas Negeri Padang by examining three main aspects: cognitive, affective, and conative. This research employs a descriptive qualitative approach with methods of observation, in-depth interviews, and documentation. Informants were purposively selected, consisting of librarians and active visitors. Data collection was conducted over two months with the researcher’s direct presence at the location, and data were analyzed through data reduction techniques, data presentation, and conclusion drawing. The results show that, cognitively, visitors' understanding of the corner's functions varies, and librarians have not actively engaged in the management of these services. Affective responses indicate interest in the design and themes of the corner; however, a lack of information and guidance has led to dissatisfaction. Conatively, only a portion of visitors actively utilizes the facilities and participates in literacy activities. The conclusion of this study emphasizes that the effectiveness of corner services heavily relies on understanding, librarian involvement, and appropriate promotional strategies to optimally meet users' information needs.